2022
DOI: 10.3389/fspor.2022.915210
|View full text |Cite
|
Sign up to set email alerts
|

Movement characteristics during customized exergames after total knee replacement in older adults

Abstract: IntroductionThere is limited understanding of how older adults can reach kinematic goals in rehabilitation while performing exergames and conventional exercises, and how similar or different the kinematics during exergaming are when compared with conventional therapeutic exercise with similar movement. The aim of this study was to describe the movement characteristics performed during exercise in custom-designed exergames and conventional therapeutic exercises among patients who have undergone unilateral total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… Chu et al (2022) report that despite being a very promising activity, more robust studies are needed to determine the effects of exergaming on physical health, as well as cognitive and quality of life outcomes. However, Janhunen et al (2022) and Cikajlo et al (2020) showed significant results about the importance of exergames for our physical health, included related to balance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… Chu et al (2022) report that despite being a very promising activity, more robust studies are needed to determine the effects of exergaming on physical health, as well as cognitive and quality of life outcomes. However, Janhunen et al (2022) and Cikajlo et al (2020) showed significant results about the importance of exergames for our physical health, included related to balance.…”
Section: Discussionmentioning
confidence: 91%
“…Chu et al (2022) report that despite being a very promising activity, more robust studies are needed to determine the effects of exergaming on physical health, as well as cognitive and quality of life outcomes. However, Janhunen et al (2022) and Cikajlo et al (2020) showed significant results about the importance of exergames for our physical health, included related to balance. Treml et al (2013), when analyzing the effectiveness of conventional proprioceptive training in the control group (trampoline, skateboard, board, swing and twist disc) and modified proprioceptive training (adapted and differentiated exercises) associated with the Nintendo Wii in the interventional group, have not reported significant changes in fear of falling (FES-I), and balance in the intervention group.…”
Section: Balancementioning
confidence: 91%
“…These prototypes, called 'Reach Game', 'Hit-it' and 'Watch-Out', required users to complete coordinated upper and lower limb movements, trunk movements and lateral displacements to achieve the goals set in the games. Similarly, Janhunen et al, (2022) also present ten exergames custom-designed for older users who needed rehabilitation for post-operative knee replacement. Each exercise included a story explaining the goal of the game and the participants' body movements, tracked by the Kinect sensor, which acted as a game controller and was translated to the screen to move the avatar.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a pilot study with laboratory loading measurements before RCT to ensure safe and reasonable exergaming for patients recovering from TKR [ 44 ]. The universities insured the participants of the duration of laboratory measurements and trips directly related to them.…”
Section: Methodsmentioning
confidence: 99%